Rodinný dům - Netočný, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce se zabývá projektové dokumentace rodinného domu v obci Litvínovice. Objekt je situován do místní zástavby. Je navržen jako tří podlažní s podsklepením, ze systému Porotherm. Střecha je plochá jednoplášťová. Objekt má tvar obdélníku.

Bachelor thesis deals with a project documentation of family house. Location in Litvíno-vice. The object is situated in the regional development. The object is designed as a three-storey, with basement, from the system Porotherm. The roof is flat, single casing. Object has a shape of rectangle.
Family house
Keywords: Rodinný dům; Litvínovice; třípodlažní; podsklepený; Porotherm; plochá střecha.; family house; location Litvínov; three storey; basement; Porotherm; flat roof.